Zu einer ägyptisch-koptischen Analogie in den "Apophthegmata Patrum" und der "Vita Pachomii": der Dorn als Sinnbild für Unbill, Schwierigkeiten, Widrigkeiten - Bojowald, Stefan (Journal of Coptic studies, 2022)
In this contribution, a further parallel between the Old Egyptian and Copticliterature is pointed out. In the specific case, the metaphorical interpretation of the thorn as a symbol for difficulties or mishap is treated. The phenomenon can be observed in two Coptic and one Egyptian text passages.